OSTEOPOTENTIAL BONE IMPLANT CONTAINING POROUS BIPHASIC CALCIUM PHOSPHATE IMPREGNATED WITH CASEIN, EGG YOLK AND ORMOCARPUM SENNOIDES - AN IN VITRO STUDY - S.SRIVIDYA,; T.P.SASTRY,; B.SANTHOSH KUMAR,; T.HEMALATHA, (International Journal of Pharma and Bio Sciences, 2015)
A novel bone implant material containing biphasic calcium phosphate (BCP), casein (CA), hen egg yolk (EY) and the extracts of Ormocarpum sennoides (Os) plant was prepared. It has shown porosity, biocompatibility, cytocompatibility and better alkaline phosphatase activity that is required for osteoinduction. In vitro studies using SaOs-2 cell line have exhibited the osteoinductive nature of the implant. These results indicate the possible use of this implant bone tissue engineering.